A Web-based survey among adults aged 40-54 years was time effective and yielded stable response patterns - Weigl, Korbinian; Hoffmeister, Michael; Brenner, Hermann (Journal of clinical epidemiology, 2019)
Objective: We want to present information about response patterns obtained by Web-based survey in a large-scale epidemiological study. Study Design and Setting: Within the RAPS (Risk Adapted Prevention Strategies for colorectal cancer [CRC]) study, we invited 160,000 randomly selected persons aged 40-54 years in three large German cities from 2015 to 2016 to complete a Web-based questionnaire on CRC risk factors and screening (97 items, average time for completion 15 minutes). Invitation letters and up to two reminder letters were sent to each individual. Results: A total of 21.4% of women and 18.0% of men completed the questionnaire. Overall cumulative response rates were 7.5%, 14.3%, and 19.6% after the initial invitation letter, and the first and second reminder, respectively, with prevalence of and associations of key epidemiological parameters (such as family history of cancer, previous colonoscopy, etc.) being remarkably stable across waves of responses. For example, the sex and age distribution of the sample did not change with additional answers gained from additional letters. Conclusion: Web-based questionnaires are feasible, cost-effective, and time effective in the setting of large-scale epidemiological studies. Although response patterns were remarkably stable over several rounds of reminders with substantially increasing cumulative response rates, future research should address possibilities to further enhance response rates.
Gesehen am 13.02.2019
Published online: 6 September 2018